EVALUATING PERFORMANCE TO IMPROVE CONTAINER THROUGHPUT AND BUSINESS STRATEGIC DECISION FOR NILAM MULTIPURPOSE TERMINAL PORT OF TANJUNG PERAK - Perdana Kusuma, Bambang
Tanjung Perak Port as one of the ports managed by Pelindo 3 has an important role in the economic development of the region of East Java Province, especially Surabaya and its surroundings. Nilam Multipurpose Terminal, which serves domestic containers, experienced a stagnant in throughput realization from 368,938 TEUs in 2017 to 329,515 TEUs in 2018 or down by 39,423 TEUs, when the domestic container throughput in the Tanjung Perak region grew 147,457 TEUs. Globally, domestic container throughput in the Tanjung Perak region has grown by 5% in the 2014-2018 period. While the growth of the Nilam Terminal container throughput in the period of 2014-2018 was only 3%. This study aims to find the root cause of not optimal (stagnant) performance that aims to increase throughput optimally and the right business strategy for the future of Nilam Multipurpose Terminals by using Fishbone Analysis, External & Internal Analysis, and SWOT analysis. Based on the exploration it can be concluded that the high Vessel Turnover Time that occurs in Nilam Multipurpose Terminal is a cause that should be evaluated and optimized so that it can increase throughput in the future. Based on Fishbone Analysis result, it can be seen that there are several factors that cause the high vessel turnover time. External Analysis and Internal Analysis are input for SWOT Analysis. From the problem scoring, the problem that become the core for increasing container throughput of Nilam Multipurpose Terminal is high vessel turnover time. From mapping of alternative solutions and quantitative comparison matrix, the result show that solution that can be done in the near future and have a significant impact to increase container throughput of Nilam Multipurpose Terminal is execute workshop and training to improve and evaluate the capabilities and skills of human resources serving in Nilam Multipurpose Terminal and Port Operation Command Center (POCC) team. Therefore, this study will have an impact on decreasing vessel turnover time so that it increases ship's call which impacts on increasing throughput.